Cultura da conexão e segunda tela: a expansão dos laços sociais por meio da interação - Sousa, Adriélle Lopes de (Universidade do Vale do Rio dos Sinos, 2016)
The studies that cover the concepts about social bond have been discussed by several authors in different areas of knowledge. With the intention of understanding the expansion of social bond in the digital environment, it is pertinent to discuss the issue based on an exploratory analysis of the behavior of the users of the social network Twitter during the transmission of a TV show Amor E Sexo, therefore, this research consists of a case study. For this, this research was based on the concepts of McLuhan (1979), Wolton (1996), Proulx and Shepatin (2012), Castells (1999), Robert. K. Yin (2001), Recuero (2009), Shirky (2011) and Jenkins, Green and Ford (2014). It was verified that the expansion of the social bond is amplified from the complementarity between the media
Keywords: Segunda tela; Laço social; Rede social; Televisão; Second screen; Social bond; Social network; TV